Analysis Of Art Workers' Creativity In Maintaining Existence In The Arts Environment Of Galur Sari Karawang - Sri Damaianti Rahmat Sugiana; Budi Rismayadi; Wike Pertiwi (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — This research aims to analyze how the creativity of Galur Sari artists helps in maintaining its existence. Research method—The author used a descriptive qualitative method and triangulation technique. Data was obtained through direct observation and interviews with five individuals. Result— The results show that the creativity of artists in Galur Sari is reflected through four aspects: fluency of thought, flexibility of thought, elaboration, and originality. Most performers utilize a collaborative approach, combining music with existing facilities, updating stage layouts with modern dance, and leveraging social media and the surrounding environment. Conclusion— Increased creativity among traditional performers can help maintain the existence of their business in the modern era and provide motivation to continue developing creativity for business sustainability.